Electric Cooking Diary in Bangladesh: Energy Requirement, Cost of Cooking Fuel, Prospects, and Challenges - Avijit Saha; Md. Abdur Razzak; M. Rezwan Khan (Energies, 2021)
Detrimental effects exerted by biomass-based traditional cookstoves on health, environment, hygiene, and the soaring price of gas makes it imperative to investigate the feasibility of electric cooking as a promising clean cooking fuel in the context of Bangladesh. However, the adoption of electric cooking is unlikely to be welcomed if the monthly cost of electricity consumed by the electric cooking appliances is not comparable to traditional cooking fuels. So far, no study has been reported in this respect. Therefore, this paper is aimed to assess the energy consumption of available electric cooking appliances for cooking typical Bangladeshi dishes. Estimated monthly electricity cost of electric cooking is also reported and then compared to that of traditional cooking fuels. For the study purpose, three respondent families were provided with a rice cooker, hot plate, induction cooker and electric pressure cooker for cooking their daily meals. After four months of use, data related to dish cooked, amount of food, cooking time, and energy consumption were collected which shows that hot plate and rice cooker were the least preferred appliances due to their poor workmanship and limited use respectively. On the contrary, despite the fact that electric pressure cookers cannot perform all types of frying, it was the most preferred appliance owing to its ability to significantly reduce the cooking time and its less energy consumption. Induction cooker was less preferred for the additional requirement of compatible cook pots. The study also reveals that monthly energy requirements for electric cooking varied from 72–87 kWh corresponding to a cooking electricity bill ranging from BDT 504–609 per month (USD 6–7.5) which is less expensive as compared with biomass and LPG based cooking. This paper also highlights the prospects and challenges associated with the adoption of electricity as the primary cooking fuel in Bangladesh.